Effectiveness of Line communication application as a social media on changes in tooth brushing behavior of junior high school students in Banjarmasin - Widodo Widodo; Darmawan Setijanto; Agung Sosiawan (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: There were only 10.7% of junior school students in Banjarmasin brushing their teeth before bedtime. Using Line (as one of the social media) can be assumed as an effective strategy to spread information. Purpose: This study aimed to reveal changes in tooth brushing behavior before bedtime in students of class VII in all state junior high schools in Banjarmasin after receiving information disseminated through Line. Method: Pre and post test technique with control group design was used in this research. Result: One week before the treatment, the mean frequency of tooth brushing behavior before bedtime in the Line group was 1.90, while in the poster group was 1.93. During the treatment, the mean frequency of tooth brushing behavior before bedtime in the Line group was 4.78 in the first 7 days, 5.07 in the second week, and 5.67 in the third week. On the other hand, the mean frequency of tooth brushing behavior before bedtime in the poster group was 4.66 in the first 7 days, 4.61 in the second week, and 5.18 in the third week. Conclusion: Messages/ information disseminated through both of Line and poster can give a significant change in tooth brushing behavior before bedtime. Nevertheless, Line can trigger better effectiveness than poster in stimulating a change in tooth brushing behavior before bedtime.